Analisis Dinamik Fondasi Mesin Generator Sets pada Power House Building Project Lube Oil Blending Plant - Isti Radhista Hertiany; Hary Christady Hardiyatmo; Fikri Faris (Jurnal Tekno Global, 2019)
ABSTRACTGenerator set machine foundations in the Power House Building Project Lube Oil Blending Plant is located on Cilegon Industrial Estate Area (KIEC), Banten. Machine foundation is analyzed in three conditions to check the safety condition against the dynamic load. The first condition is the existing condition where the block foundation is not embedded in the ground. From the results of the analysis of this condition, the natural frequency value is 20,077 Hz. It is very close to frequency of machine foundation, although it is safe from resonance. The vertical and horizontal amplitude is safe because smaller than permission amplitude. In the second condition, the effect of the embedded block foundation is checked, the smaller natural frequency value 13,305 Hz is safe against resonance. The amplitude value obtained is also smaller. In the last condition analyzed the embedded block foundation without using piles to determine the effect of piles during the machine foundation system. Although the results of the analysis obtained a smaller natural frequency value of about 10,628 Hz but seen from its value of vertical and horizontal amplitude, the foundation without pile is not safe. In general, it can be concluded that the existing foundation is safe from dynamic load, but it would be better if the foundation of the block is embedded on the ground. The use of piles can reduce the amplitude value of machine foundation.Keywords : machine foundation, dynamic analysis, generator setsABSTRAKFondasi mesin generator sets pada Power House Building Project Lube Oil Blending Plant berlokasi di Kawasan Industrial Estate Cilegon (KIEC), Banten. Analisis fondasi mesin dilakukan dengan tiga kondisi untuk mengecek keamanan fondasi terhadap beban dinamik. Kondisi pertama adalah kondisi eksisting dimana fondasi blok tidak tertanam dalam tanah. Dari hasil analisis kondisi ini didapatkan nilai frekuensi natural 20,077 Hz. Frekuensi natural tanah ini mendekati nilai frekuensi mesin, walaupun masih saman dari resonansi. Nilai amplitudo vertikal dan amplitudo horizontal aman karena lebih kecil dari nilai amplitudo izin. Pada kondisi kedua dicek pengaruh fondasi blok tertanam dan dihasilkan nilai frekuensi natural yang lebih kecil yakni 13,305 Hz dan aman terhadap resonansi. Nilai amplitudo yang didapat juga lebih kecil. Pada kondisi terakhir dianalisis fondasi blok tertanam tanpa menggunakan pile untuk mengetahui pengaruh pile pada sistem fondasi mesin. Walaupun dari hasil analisis didapat nilai frekuensi natural yang lebih kecil yakni sekitar 10,628 Hz, namun dilihat dari nilai amplitudo vertikal dan amplitudo horizontalnya, fondasi tanpa pile ini tidak aman. Secara umum dapat disimpulkan bahwa fondasi eksistingaman terhadap gaya dinamik, namun akan lebih baik jika fondasi blok tertanam dalam tanah. Penggunaan pile mampu memperkecil nilai amplitudo pada fondasi mesin.Kata kunci : Fondasi mesin, analisis dinamik, generator sets